Bromelain Inhibits Allergic Sensitization and Murine Asthma via Modulation of Dendritic Cells. (5th December 2013) - Secor, Eric R.; Szczepanek, Steven M.; Castater, Christine A.; Adami, Alexander J.; Matson, Adam P.; Rafti, Ektor T.; Guernsey, Linda; Natarajan, Prabitha; McNamara, Jeffrey T.; Schramm, Craig M.; Thrall, Roger S.; Silbart, Lawrence K.
Abstract : The incidence of atopic conditions has increased in industrialized countries. Persisting symptoms and concern for drug side-effects lead patients toward adjunctive treatments such as phytotherapy. Previously, we have shown that Bromelain (sBr), a mixture of cysteine proteases from pineapple, Ananas comosus, inhibits ovalbumin (OVA)-induced murine model of allergic airway disease (AAD). However, sBr's effect on development of AAD when treatment is administered throughout OVA-alum sensitization was unknown and is the aim of the present study. C57BL/6J mice were sensitized with OVA/alum and challenged with 7 days OVA aerosol. sBr 6 mg/kg/0.5 ml or PBS vehicle were administered throughout sensitization. Lung, bronchoalveolar lavage (BAL), spleen, and lymph nodes were processed for flow cytometry and OVA-specific IgE was determined via ELISA. sBr treatment throughout OVA-alum sensitization significantly reduced the development of AAD (BAL eosinophils and lymphocytes). OVA-specific IgE and OVA TET + cells were decreased. sBr reduced CD11c + dendritic cell subsets, and in vitro treatment of DCs significantly reduced CD44, a key receptor in both cell trafficking and activation. sBr was shown to reduce allergic sensitization and the generation of AAD upon antigen challenge. These results provide additional insight into sBr's anti-inflammatory and antiallergic properties and rationale for translation into the clinical arena.